2019
DOI: 10.3171/2019.1.focusvid.18447
|View full text |Cite
|
Sign up to set email alerts
|

CTA-guided outflow-targeted embolization of direct carotid-cavernous fistula

Abstract: This video presents a case of new-onset visual blurring, diplopia, and conjunctival injection after head injury. CTA of the brain revealed a direct carotid-cavernous fistula (dCCF) of the right side. Careful evaluation of CTA source images revealed that the fistula point was at the ventromedial aspect of the right cavernous internal carotid artery (ICA), about 3.6 × 3.6 mm2 in size, with 3 main outflow channels (2 intracranial and 1 extracranial) (CTA-guided concept). DSA of the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although entire occlusion of the SOV with coils was presented as illustrative cases in some studies, it has not been described in detail. 15,25 Liao et al 26 reported direct CCF treated with CT angiography-guided venous outflow-targeted coil embolization and described the advantages of outflow-targeted embolization as follows. First, embolization of the venous outflow first can keep the ICA visualized without being obscured by the embolic material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although entire occlusion of the SOV with coils was presented as illustrative cases in some studies, it has not been described in detail. 15,25 Liao et al 26 reported direct CCF treated with CT angiography-guided venous outflow-targeted coil embolization and described the advantages of outflow-targeted embolization as follows. First, embolization of the venous outflow first can keep the ICA visualized without being obscured by the embolic material.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the advantage that Liao et al 26 reported, another advantage exists concerning venous outflow-targeted coil embolization. When the engorged veins were occluded, the venous outflow pathway would be eliminated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation